Management of biventricular assist device implantation in patients with necrotic pancreatitis - Gertner, Victor; Bordel, Viktor; Tochtermann, Ursula; Kallenbach, Klaus; Verch, Markus; Ungerer, Matthias; Piontek, Patricia; Arif, Rawa; Hasani, Mohammad Reza Mohammad; Takahashi, Hiroaki; Farag, Mina; Ruhparwar, Arjang; et al. (The heart surgery forum, 2010)
This report describes the management of biventricular assist device (BIVAD) implantation in a patient with necrotic pancreatitis. BIVADs provide mechanical support for ventricular ejection in the failing heart and have become an accepted treatment for end-stage heart failure. They also have proved to be a successful bridge to heart transplantation. As their popularity has grown, the number of patients with BIVADs presenting for noncardiac surgery is increasing. We report the successful management of an implanted extracorporeal BIVAD in a patient with end-stage heart failure and with pancreatic stents in a case of necrotic pancreatitis. Historical, physical, laboratory, and imaging data allowed conservative management leading to a favorable outcome.